EFEKTIVITAS MODEL PEMBELAJARAN ROLE PLAYING TERHADAP PENINGKATAN MAHARAH KALAM SISWA KELAS VIII DI MTSN 2 MOJOKERTO - Sitti Robbani; Muqimah Liwais Sunnah (Institut Kariman Wirayudha Sumenep Madura, 2025)
Teaching Maharah Kalam often faces challenges in formal non-Pesantren educational institutions such as MTsN 2 Mojokerto. This condition makes maharah kalam learning less interesting, inactive, rigid, and ultimately boring. One important component in teaching and learning activities is the learning model. Role Playing Model is a method of mastering material through the development of students' imagination and appreciation. Based on this, this study raises the issue